2014
DOI: 10.1371/journal.pone.0104553
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Potato (Solanum tuberosum L.) MKK6 in Response to Potato virus Y

Abstract: Mitogen-activated protein kinase (MAPK) cascades have crucial roles in the regulation of plant development and in plant responses to stress. Plant recognition of pathogen-associated molecular patterns or pathogen-derived effector proteins has been shown to trigger activation of several MAPKs. This then controls defence responses, including synthesis and/or signalling of defence hormones and activation of defence related genes. The MAPK cascade genes are highly complex and interconnected, and thus the precise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…They are implicated in the signaling of plant developmental programes and response to multiple environmental stressors s and they are a core mediator for HR-associated PCD (reviewed by [60]). Specifically, the MAPK signaling network in HR-conferred resistance to PVY involves MAPK kinases 6 (MKK6) and the downstream targets MAPK4_2 (orthologue of AtMAPK4, -11 and -12), MAPK6 (orthologue of AtMAPK6), and MAPK13 (orthologue of AtMAPK13) [61]. Downregulation of MKK6 was shown to increase PVY concentrations in infected plants, confirming that this kinase is an important component of potato immunity against the virus [62].…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 88%
“…They are implicated in the signaling of plant developmental programes and response to multiple environmental stressors s and they are a core mediator for HR-associated PCD (reviewed by [60]). Specifically, the MAPK signaling network in HR-conferred resistance to PVY involves MAPK kinases 6 (MKK6) and the downstream targets MAPK4_2 (orthologue of AtMAPK4, -11 and -12), MAPK6 (orthologue of AtMAPK6), and MAPK13 (orthologue of AtMAPK13) [61]. Downregulation of MKK6 was shown to increase PVY concentrations in infected plants, confirming that this kinase is an important component of potato immunity against the virus [62].…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 88%
“…Since plant promoter information is still scarce, so far the compilation of native promoter sequences in the plant GenoCAD library is based on identification and characterization of several Solanum tuberosum promoters performed in our research group (e.g. StMKK6 promoter [ 21 ]). However, the idea is that each user expands the library with new entries of experimentally characterized promoters of interest [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 108 sequences from potato, 63 from eggplant, 79 from pepper, and 64 from coffee have been reported in this study based on perfectly conserved signature motifs belonging to the three major families of the MAPK cascade. Although, few members of some of these families were reported recently ( Daigle & Matton, 2015 ; Kong et al, 2012 ; Lazar et al, 2014 ; Liu et al, 2015 ; Mohanta et al, 2015 ; Wu et al, 2014 ), this articles reports the largest set of genes identified from all three of these gene families and their further subfamilies in the said species. Phylogenetic analysis of the reported sequences shows the conservation of the genes throughout the Solanaceae plant family and coffee, which is closely related to Solanaceae species in terms of its genetic make-up.…”
Section: Resultsmentioning
confidence: 89%
“…Identification of the three complete families of the MAPK cascade has not been done earlier in potato, eggplant, pepper, and coffee. However, being widely studied due to their vital functions, a few of these genes have recently been identified and reported as MPK, MKK, and MAPKKK in tomato ( Daigle & Matton, 2015 ; Kong et al, 2012 ; Lazar et al, 2014 ; Mohanta et al, 2015 ; Wu et al, 2014 ); as MPK, MKK, and MEKK-like from MAPKKK in potato ( Daigle & Matton, 2015 ; Lazar et al, 2014 ; Mohanta et al, 2015 ); and, as MPK and MKK in pepper ( Liu et al, 2015 ). However, genome identification of the three complete gene families hasn’t been reported for any one of them; thus, such an identification will be a huge step forward towards unraveling their functionality and importance.…”
Section: Resultsmentioning
confidence: 99%